Analisis Faktor-Faktor yang Mempengaruhi Penawaran Tenaga Kerja di Sumatera Utara - Margaretha, Dewi; Purba, Kristin Yenita; Karo-Karo, Laura Elfina; Zebua, Nobel Indah Clawdya; Berliana, Zenifer Feby; Rinaldi, Muamar; Rozaini, Noni (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This research aims to determine the effect of population and wages on labor supply in North Sumatra. This analysis uses the panel data method. The research results show that: (1) population has a positive and significant influence on labor supply in North Sumatra. (2) wages have a positive and significant influence on labor supply in North Sumatra. Together population and wages have a significant influence on labor supply in North Sumatra. (3) population and wages both have a positive and significant effect on labor supply in North Sumatra